ANALISIS FRAUD PENTAGON DALAM MENDETEKSI FRAUDULENT FINANCIAL REPORTING DENGAN MENGGUNAKAN FRAUD SCORE MODEL (Studi Empiris Pada Perusahaan Perbankan Yang Terdaftar Di BEI Pada Tahun 2015- 2018) - Salsabila Nanda; Ratnawati Vince; Paulus Sem (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study was aimed to examine the effect of financial target, financial stability, external pressure, ineffective monitoring, change in auditor, change in director, frequent number of CEO’s picture, dan dualism position on fraudulent financial reporting. The population of this study worebankingcompanies listed on the Indonesian Stock Exchange period 2015to 2018. The determined by purposive sampling method where 29banking companies were used as sample. The total sample is 116 companies. The data source used in the study was the secondary data. Analysis of data is carried out using multiple regression analysis with the program of SPSS version 23 for windows. The result of this research show that financial target and frequent number of CEO’s pictures significantly has a positive effect towards fraudulent financial reporting. While financial stability, external pressure, ineffective monitoring, change in auditor, change in directors,and dualism position does not significantly affect the fraudulent financial reporting.Keywords: Fraudulent Financial Statement, Fraud Pentagon, Financial Target, Financial Stability, External Pressure, Ineffective Monitoring, Rationalization, Capability, and Arrogance